Utilization of Centrosema Legume as a Nutrient-Rich Forage for Sustainable Livestock Systems - Rezki Amalyadi (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2026)
Livestock production systems in tropical regions face increasing pressure to improve feed quality while maintaining environmental sustainability and reducing dependence on external inputs. Forage legumes offer a viable strategy to address these challenges by enhancing nutritional value and delivering key ecosystem services. This study evaluated the agronomic performance, forage yield, and nutritional characteristics of Centrosema pubescens as a nutrient-rich forage legume within sustainable livestock systems. A field experiment was conducted using a randomized complete block design with three replicates under tropical conditions representative of smallholder production environments. Forage biomass was harvested at the peak vegetative stage and analyzed for dry matter yield, crude protein, fiber fractions, and mineral content using standard laboratory procedures. The results showed that Centrosema produced substantial biomass, exceeding 5 t ha?¹ of dry matter, indicating strong adaptation and productive capacity under low-input management. Nutritional analysis revealed high crude protein concentrations (18–22%) and moderate fiber levels, supporting its suitability as a protein supplement for ruminant diets dominated by low-quality grasses. Integration of Centrosema into grass-based systems improved overall forage quality and contributed to enhanced soil nitrogen availability through biological nitrogen fixation, thereby reinforcing nutrient cycling and soil health. Conceptual analysis further highlighted the role of grass–legume mixtures in promoting rhizosphere stability and sustaining forage productivity. Overall, the findings confirm that Centrosema pubescens is a promising forage legume for improving feed quality, supporting soil fertility, and advancing the sustainability of tropical livestock production systems. Further studies incorporating animal performance trials are recommended to fully quantify its impact on ruminant productivity.